Levonorgestrel Ameliorates Adenomyosis via lncRNA H19/miR-17/TLR4 Pathway - Liang N; Zhang W; Wang H; Shi W; Wang L; Ma L (Dove Medical Press, 2020)
Na Liang,1,* Wenfeng Zhang,2,* Hongjiang Wang,3 Wei Shi,4 Li Wang,2 Lijuan Ma2 1Department of Traditional Chinese Medicine, The First Affiliated Hospital of Shandong First Medical University, Shandong Provincial Qianfoshan Hospital, Shandong University, Jinan City, Shandong Province, People’s Republic of China; 2Department of Obstetrics and Gynecology, The First Affiliated Hospital of Shandong First Medical University, Shandong Provincial Qianfoshan Hospital, Jinan City, Shandong Province, People’s Republic of China; 3TCM Gynecology Department, Maternal and Child Health Hospital, Dezhou City, Shandong Province, People’s Republic of China; 4Department of Gynecology, Affiliated Hospital of Shandong University of Traditional Chinese Medicine, Jinan City, Shandong Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Li Wang; Lijuan MaDepartment of Obstetrics and Gynecology, The First Affiliated Hospital of Shandong First Medical University, Shandong Provincial Qianfoshan Hospital, No. 16766, Jingshi Road, Lixia District, Jinan City, Shandong Province, People’s Republic of ChinaTel +86-15969718268; +86-13791056924Email yijieru95825815814@163.com; yaku4AHNQXhnrx7AHK@163.comPurpose: To explore the mechanism of levonorgestrel (LNG)-ameliorating adenomyosis through long non-coding RNA H19 (lncRNA H19)/miR-17/Toll-like receptor 4 (TLR4) pathway.Patients and Methods: A total of 71 cases of adenomyosis and 54 cases of normal endometrium were sampled. Quantitative polymerase chain reaction (qPCR) was employed to quantify lncRNA H19, miR-17, and TLR4 mRNA, while Western blot (WB) was used to quantify TLR4 protein. Effects of LNG on normal endometrial stromal cells (ESCs) were evaluated. Suppression/over-expression vectors of lncRNA H19, miR-17, and TLR4 were constructed to observe their effects on ESCs.Results: MiR-17 and TLR4 mRNA were up-regulated and lncRNA H19 was down-regulated in adenomyosis. After LNG treatment, lncRNA H19 was up-regulated while miR-17 and TLR4 were down-regulated. LNG, up-regulation of lncRNA H19, and down-regulation of miR-17 and TLR4 portend increased apoptosis, G1-arrested cells, as well as inhibited inflammation. Dual-luciferase reporter (DLR) assay conformed the targeting relation of lncRNA H19/miR-17/TLR4 pathway.Conclusion: LNG ameliorates adenomyosis via lncRNA H19/miR-17/TLR4 pathway.Keywords: adenomyosis, levonorgestrel, lncRNA H19/miR-17/TLR4 pathway